PROFIL KEBUGARAN JASMANI SISWA KELAS V DAN VI MELALUI INSTRUMEN TES KEBUGARAN JASMANI INDONESIA (TKSI) FASE C DI SD NEGERI 178492 PAGAR BATU - Hutagalung, Novan Trisan; Khairul Usman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the physical fitness profile of 5th and 6th-grade students at SD Negeri 178492 Pagar Batu based on the Indonesian Student Fitness Test (TKSI) Phase C instrument. This descriptive quantitative research applied a one-shot case study approach. The research population included all 58 students in grades 5 and 6. Total sampling was utilized to select the sample. Data collection involved five components of the TKSI Phase C test: the Child Ball Test, Tok-Tok Ball Test, Move The Ball Test, Shuttle Run Test, and 600-Meter Run Test. Data analysis was conducted using descriptive quantitative statistics in the form of percentages. The results showed that the students' physical fitness profile was generally in the